Windows Live essentials and services using free Microsoft applications for Windows 7 - Jones, Bradley (Wiley Pub., 2009)
A full-color, step-by-step guide for using the most popular free software and online offerings from Microsoft's new Windows Live Essentials Microsoft's new operating system - Windows 7 - isn't including many applications you might be used to seeing. Instead, those applications are being made available as set of free downloads called Windows Live Essentials, with the promise of more frequent updates independent of when the operating system releases happen. Windows Live Essentials includes tools such as Messenger, Mail, Writer, Photo Gallery, and Movie Maker. This valuable guide shows you how to use these applications so that you accomplish everyday tasks successfully and smartly. Step-by-step instructions show you how to use not only these applications, but also associated Windows Live on-line services. As an example, you'll learn just how easy it is to create panoramic pictures in seconds or how to create movies from pictures in just a few minutes. Then you'll get the inside scoop on how to communicate and share using Messenger, SkyDrive, Spaces, and Groups. Windows Live Essentials are available as free downloads for the Windows 7, Windows Vista, and Windows XP operating systems Reviews what is included Windows Live products such as Messenger, Mail, Writer, Photo Gallery, Movie Maker as well as Windows Live services like Spaces, Groups, SkyDrive, Calendar, and Events Provides you with essential information on using the applications and services efficiently in order to accomplish everyday tasks. With this book, you'll quickly be on your way to accessing these useful applications in an effort to making your life easier.
Includes index. - Print version record
Keywords: Microsoft Windows (Computer file); Computer programs; Free material; Microcomputers -- Programming; Computer software; Logiciels; Matériel gratuit; Micro-ordinateurs; Programmation; software; REFERENCE; General; Microcomputers; Programming